'He was just your typical average guy' Examining how person descriptions are elicited by frontline police officers. Issue 2 (1st January 2021) - Dalton, Gary; Milne, Rebecca; Hope, Lorraine; Vernham, Zarah; Nunan, Jordan
Summary: Person descriptions often lack the level of detail necessary to assist in the apprehension of a perpetrator. To date, it is not clear how person descriptions are obtained by frontline police officers. Worldwide, many police forces now use body worn video (BWV), which provides a unique opportunity to examine how frontline police officers gather person descriptions from witnesses. We examined how person descriptions ( N = 207) were elicited by frontline police officers, with a particular focus on the types of questions used. BWV of 81 interactions involving 45 frontline police officers and 141 witnesses were analysed. Person descriptions were obtained using inappropriate questions 50.54% of the time, with leading questions being the most commonly used (44.84%). Appropriate questions (i.e., open questions) led to more information being provided (cf. inappropriate questions), including more fine‐ and coarse‐grain details. Implications for the training of frontline police officers are discussed.